Concepts of epidemiology integrating the ideas, theories, principles and methods of epidemiology - Bhopal, Raj S. (Oxford : Oxford University Press, 2008)
This text explains and illustrates the key concepts, language, principles and methods that underpin the science of epidemiology and its applications to policy making, health service planning and health promotion.
Previous ed.: 2002.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology